PENGGUNAAN SISTEM APLIKASI OUT OF GAUGE DENGAN BAGGAGE HANDLING SYSTEM PADA TERMINAL 3 ULTIMATE DOMESTIK DI BANDARA SOEKARNO- HATTA - I Made Adnyana; Suan Nauli; Mustika Sari (Institut Transportasi dan Logistik Trisakti, 2018)
This research was aimed at finding out the effect of one application system to the other app system. To solve the problems, the researchers were using two kinds of data collecting methods which were field research (observation and interview) and library research. The researchers were using descriptive comparative to analyze the data collected. The data taken was qualitative data. The data sources were primary data from observation and interview and secondary data from books, journals, reports, and others. The result shows that there is a large discrepancy between the two systems application: out of gauge and baggage handling. It is due to lack of facilities of out of gauge app and unclear SOP (standard operating procedure) and lack of baggage safety of baggage handling system. For the last part, it is because of bad conveyor structures though baggage handling system is considered still better than the out of gauge app.